Hodnocení finanční situace podniku a návrhy na její zlepšení - Tolkner, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Bakalářská práce se zaměřuje na zhodnocení finanční situace společnosti STROJÍRNA OSLAVANY, spol. s r. o. v letech 2015-2019. Na základě zhodnocení vybraných finančních ukazatelů obsahuje zpracování finanční analýzy společnosti, vyhodnocení společnosti z hlediska finančního zdraví, za pomocí analýz externích vlivů identifikuje příležitosti pro zlepšení situace podniku na trhu

The bachelor´s thesis is focused on the evaluation of the financial situation of the company STROJÍRNA OSLAVANY, spol. s r. o. in 2015-2019. Based on the evaluation of selected financial indicators this thesis contains the elaboration of the financial analysis of the company, the evaluation of the company in terms of financial health, using the analysis of external influences identifies opportunities for improving the company's market situation
Evaluation of the Financial Situation of a Company and Proposals for its Improvement
Keywords: Finanční analýza; finanční ukazatele; rozvaha; výkaz zisku a ztrát; aktiva; pasiva; likvidita; rentabilita; zadluženost; Financial analysis; financial indicators; balance sheet; profit and loss account; assets; liabilities; liquidity; profitability; indebtedness